Minyak Pati Beberapa Bahagian Pokok Goniothalamus ridleyi (Essential Oils from Different Parts of Goniothalamus ridleyi Plant) - Samsiah, Jusoh; Fasihuddin Badruddin, Ahmad; Laily, Din; Zuriati, Zakaria (Penerbit UKM, 2015)
The essential oils of fresh and dried samples of stem bark, stem, fruit, root and leaf of Goniothalamus ridleyi were extracted using hydrodistillation. They were examined by capillary GC and GC-MS. The chemical constituents were identified by comparison of their mass spectral data with those from the Wiley library, their retention indices and co-injection with the authentic samples. A total of 50 compounds representing 89.5% of the essential oil content were identified from the fresh stem bark of G. ridleyi. The fresh stem bark oil was dominated by linalool (15.2%) and citronellal (10.9%). A total of 47 compounds representing 90.1% of the total oil were identified from fresh stem of G. ridleyi, with the major compounds identified as β-eudesmol (27.1%) and γ-eudesmol (20.8%). The fruit oil contain 49 identified compounds representing 89.8% of total oil with the major constituents identified as β-cubebene (20.7%) and elemol (20.2%). The chemical constituent in the fresh sample were similar to the constituent in the dried sample, except that the dried samples were found to be rich in β-caryophyllene, limonene, β-selinene, viridifloral, α-copaene and cyperene.